Pause or consonantal quiescence haa’ (haa’ al-sakt) between Qurraa’ and grammarians - Mohammad Issa Alhourani, Tar Abdallahi, (Opción, 2020)
This paper looks into the role of a significant letter of the Arabic language alphabet: haa‟ al-sakt or pause haa. This sound makes the stop process (waqf) smoother, the verbal speech euphonious, and the written forms ideal. Moreover, it makes the speaker more comfortable to articulate the sounds perfectly without giving up on certain properties of these sounds for the purpose of stopping. Since this haa‟ is used in the Holy Quran, the paper will focus on two aspects that are essential for exploring this haa‟, what it is really for and the various ways of using it.